Simplify 37x + 27x using properties of operations.
5 answers
37x + 27x = (37 + 27)x = 64x
Simplify 3/7x + 2/7x using properties of operations.
To simplify the expression, we can combine the like terms.
3/7x + 2/7x = (3/7 + 2/7) x
To combine the fractions, we add the numerators and keep the common denominator:
= (5/7) x
Therefore, the simplified expression is 5/7x.
3/7x + 2/7x = (3/7 + 2/7) x
To combine the fractions, we add the numerators and keep the common denominator:
= (5/7) x
Therefore, the simplified expression is 5/7x.
Simplify 6/7c − 5/9d − 1/2c + 1/3d.
To simplify the expression, we can combine like terms.
6/7c - 5/9d - 1/2c + 1/3d
To combine the terms with the same variables, we can find a common denominator and then add or subtract the numerators.
For the terms with "c":
The common denominator is 7 * 2 = 14.
6/7c - 1/2c
= (12/14c) - (7/14c)
= (12 - 7) / 14c
= 5/14c
For the terms with "d":
The common denominator is 9 * 3 = 27.
-5/9d + 1/3d
= (-5/9d * 3/3) + (1/3d * 9/9)
= (-15/27d) + (9/27d)
= (-15 + 9) / 27d
= -6/27d
= -2/9d
So, the simplified expression is:
5/14c - 2/9d
6/7c - 5/9d - 1/2c + 1/3d
To combine the terms with the same variables, we can find a common denominator and then add or subtract the numerators.
For the terms with "c":
The common denominator is 7 * 2 = 14.
6/7c - 1/2c
= (12/14c) - (7/14c)
= (12 - 7) / 14c
= 5/14c
For the terms with "d":
The common denominator is 9 * 3 = 27.
-5/9d + 1/3d
= (-5/9d * 3/3) + (1/3d * 9/9)
= (-15/27d) + (9/27d)
= (-15 + 9) / 27d
= -6/27d
= -2/9d
So, the simplified expression is:
5/14c - 2/9d